ANALISIS NILAI EKSPOR, SUKU BUNGA, UPAH PEKERJA, DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENANAMAN MODAL ASING DI JAWA TENGAH (PERIODE 2004:1-2013:4) - Brenda Aditama; Tripriyo Tripriyo; Fatchun Hasyim (Politeknik Negeri Semarang, 2015)
This study is intended to find out that the exports value, interest rates, labour wages, and grossregional domestic product, have an effect toward the value of foreign investment in CentralJava. The analysis techniques used in this study is the technique of multiple linear regressionanalysis with Ordinary Least Square (OLS) method, F-test for simultaneously testing and t-testfor partial testing. Results of data analysis showed simultaneously the exports value, the interestrates, the labour wages, and the gross regional domestic product that had significant effect on foreign investment in Central Jawa. F-test results show that the value of Prob (F-statistic) is 0.000214 < default values of significance (0.05) with a coefficient of determination (R2) of0.586384, which means that the variable export values, interest rates, wages, and GRDPcontribution amounting to 58,63%. The remaining 41,37% was explained by other variables.Partially, the independent variables have positive and significant impact on foreign investmentin Central Java in 2004:1-2013:4.